2011
DOI: 10.1007/s00586-011-1812-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo biostability of polymeric spine implants: retrieval analyses from a United States investigational device exemption study

Abstract: The Dynesys System for stabilizing the lumbar spine was first surgically implanted in Europe in 1994. In 2003, a prospective, randomized, investigational device exemption clinical trial of the system for non-fusion dynamic stabilization began. Polycarbonate urethane (PCU) and polyethylene terephthalate (PET) components explanted from four patients who had participated in the study were analyzed for biostability. Components had been implanted 9-19 months. The explanted components were visually inspected and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…We expected that various morphologies of OCDs would result in different mechanical and thermal properties as well as the shape‐memory behavior of PCUUs. Furthermore, OCDs have been reported to improve the biostability of polyurethanes (PURs) when compared to those based on polyesters and polyethers, which is essential for purposes of long‐term medical applications, we would like to achieve by our PCUU system …”
Section: Introductionmentioning
confidence: 99%
“…We expected that various morphologies of OCDs would result in different mechanical and thermal properties as well as the shape‐memory behavior of PCUUs. Furthermore, OCDs have been reported to improve the biostability of polyurethanes (PURs) when compared to those based on polyesters and polyethers, which is essential for purposes of long‐term medical applications, we would like to achieve by our PCUU system …”
Section: Introductionmentioning
confidence: 99%
“…The PCU spacer is based on a soft polycarbonate segment and on an aromatic polyurethane hard segment (Bionate® 55D, DSM-PTG [36]). Previous literature studies reported an average Mw around 150,000–200,000 g/mol for this material [34]. The Dynesys® spacer has a thickness of 3.6 mm and an external diameter of 12 mm.…”
Section: Methodsmentioning
confidence: 92%
“…The length of the cord depends on the number of consecutive spacer and the diameter is 4 mm. The average Mw of the PET fibers in a similar system was reported to be around 75,000 g/mol [34]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 40,000 patients have been implanted with this device since then [41], but with little published research. Thus, physicians did not report their clinical outcomes, even though the Dynesys Ò was new and its safety and efficacy had not yet been demonstrated.…”
Section: Deficiencies In the Approval Process Of The Dynesys òmentioning
confidence: 99%